(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to investigate the administered analgesics and postoperative pain in adult patients undergoing cardiac surgery. This is a retrospective study with a quantitative approach, approved by the ethics committee of UFRN (176/05). Were studied 87 patients undergoing cardiac surgery, and 42 (48.3%) were male and 45 (51.7%) females, mean age 45 ± 11 years. The instruments were a summary of therapy evaluation, consisting of socio-demographic and clinical patient data and the numerical pain scale, which ranges from zero to ten points, categorized as mild (1-3), moderate (4-7) and pain (8-10). The procedures were performed by the application of the instruments. Categorical data were subjected to descriptive statistics and the quantitative to the T Test, using SPSS version 15.0. The perception of pain was experienced and reported with magnitudes ranging from mild, moderate and intense on 1st day of postoperatively. Regarding analgesics administered was noted that only four analgesics were administered separately, with predominance of paracetamol in 46% of patients and 4.6% of patients received no analgesics. The mean of intensity painful were compared between males and females and to be submitted to the T Test showed no statistical significance. There was a variation of analgesic drug prescriptions which shows a deficiency in the consensus and use of protocols for control of postoperative pain. The pain was predominantly mild to moderate in the 1st POD.